Manajemen Sumber Daya Manusia Dalam Lingkungan Bisnis Rumah Sakit : Systematic Literature Riview - Sunari, Ari; Mulyanti, Dety (Jurnal Riset dan Inovasi Manajemen, 2023)
Hospitals are service businesses that provide intangible products such as services and involve human resources (HR) to run them. HR management is important in driving the hospital business. This article aims to find out the importance of HR management in the hospital business and its related factors, thereby creating performance improvements related to the demands of effective and efficient organizational goals. The method used is to search for previous articles with a total of 17 articles and a span of 10 years (2013-2023). The results show that good human resource management influences the desire for organizational goals by increasing performance.